2021
DOI: 10.1590/s1678-9946202163016
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of severity and chronification in chikungunya fever: a systematic review and meta-analysis

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Studies suggested that the host's immune response is crucial in controlling CHIKV infection and that dysregulated responses can be damaging to the host, as is seen in severe and chronic cases [14,30]. Several evidences have demonstrated that persistent arthralgia could be the result of the host inflammatory response and increased production of inflammatory mediators, including IFN-α, IFN-γ, TNF-α, IL-1β, IL-6, IL-7, CXCL8/IL-8, IL-10, IL-12, IL-15, IL-17, IL-27, GM-CSF, CCL2/MCP-1, and CXCL10/IP10 [47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that the host's immune response is crucial in controlling CHIKV infection and that dysregulated responses can be damaging to the host, as is seen in severe and chronic cases [14,30]. Several evidences have demonstrated that persistent arthralgia could be the result of the host inflammatory response and increased production of inflammatory mediators, including IFN-α, IFN-γ, TNF-α, IL-1β, IL-6, IL-7, CXCL8/IL-8, IL-10, IL-12, IL-15, IL-17, IL-27, GM-CSF, CCL2/MCP-1, and CXCL10/IP10 [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the low incidence of CHIKV infection we hypothesized, the absence of active cases we reported which opposes the high seroprevalence of IgG antibodies could also support the hypothesis that CHIKV circulates in the population inducing light clinical manifestation which did not required medical consultation, making difficult to catch active cases. Increase or reduce levels of several biomarkers such as cytokines or coagulation factor (factor VII) have been associated with the severity of CHIKV infection [ 41 ]. In our study area co-endemic with helminth infections known to deeply modulate the host immune system to prevent immune-mediated worm ejection [ 42 ], we can hypothesize a possible interaction between the two infections to explain the low clinical expression of CHIKV infections we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of the disease with an emphasis on the early prognosis of the neopterin can improve medical treatment in its initial phase, preventing the progression to its most severe form. Neopterin is expressed in the first days of the disease and the different concentrations of this marker may be useful to monitor the activation of the immune response [16,31]. Another study found higher values of CSF neopterin in patients with meningitis caused by viruses and bacteria compared to controls [13].…”
Section: Discussionmentioning
confidence: 99%